Poems You Ought to Know - Peattie, Elia Wilkinson, 1862-1935 (Salt Lake City, UT : Project Gutenberg, 2016)
"Poems You Ought to Know" by Elia Wilkinson Peattie is an anthology of poetry compiled in the early 20th century. The collection is aimed at rekindling a love for poetry among its readers, featuring verses from a diverse array of renowned poets. Peattie curates this selection with the hope of providing insights and beauty that uplift and inspire those who may have drifted away from lyrical appreciation. The opening of the anthology lays the groundwork for the reader's journey through poetry. It begins with an introduction emphasizing the importance of dedicating moments each day to the nurture of one's "inner life" through poetry, quoting Professor Charles Eliot Norton$1 (Bs view on its restorative powers. This introduces the objective of the collection: to inspire both new and old lovers of poetry. Following this, the contents list reveals a rich tapestry of poems from famous poets such as Wordsworth, Shakespeare, and Byron, promising a rewarding exploration of classic verses that exemplify universal themes of life, beauty, love, and mortality. (This is an automatically generated summary.)s
Release date is 2016-10-30
This etext was transcribed by Les Bowler
Keywords: English poetry; American poetry